OBTENÇÃO INDEVIDA DE DADOS SENSÍVEIS DE CONSUMIDORES E SEU USO PARA A INVASÃO DE PRIVACIDADE - Zucco Paganini, Allana Vitória; Maccarini, Bianca; Danielewicz, João Vitor; Cordova Vieira, Leandro Otavio (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2025)
Introduction: The protection of personal data has become a central concern with the rise of digitalization and the constant exchange of information online. Many organizations request data in exchange for benefits, without clarifying the purpose of the collection. There has been an increase in cases of data leaks and the sale of sensitive information, as well as violations of privacy through the unauthorized sharing of third-party data. A significant number of consumers are unaware that their data is being misused, which constitutes a criminal practice. Objective: To highlight the correlation between the improper collection of data and the privacy violations experienced by consumers. Additionally, to expose the lack of transparency in transactions involving critical data, emphasizing the limited knowledge consumers have when their data is misused. Methodology: The study involved an analysis of articles on the topic and an objective survey conducted with the public. Questions addressed issues such as the request for personal data after purchases, consumers' understanding of how their data is used, and experiences with unwanted contact. The research aimed to establish a relationship among three main stages: the provision of data in exchange for benefits, its leakage or intentional sale, and the consequences faced by consumers. Results: Over 95% of participants reported being asked for personal data after making a purchase, mostly in exchange for benefits such as discounts or loyalty program points (85%). Many respondents said they received unsolicited contact from unknown sources, which may indicate data leaks. However, not all who provided their data experienced these issues, showing that data collection alone is not solely responsible. Nevertheless, a strong correlation exists between data sharing and privacy breaches. Conclusion: Providing personal information in commercial transactions is a widespread and frequent practice. While most participants received some form of benefit in return, such as discounts or reward points, this practice raises concerns. The high number of reports about unwanted contact suggests flaws in the protection of personal data. The public’s lack of awareness about how their data—like the use of CPF on receipts—is used highlights the need for educational campaigns on consumer rights and data privacy. Therefore, it is essential to deepen the discussion about how data is collected, used, and protected, promoting greater transparency and security in consumer relations.